2017
DOI: 10.1088/1367-2630/aa8fe0
|View full text |Cite
|
Sign up to set email alerts
|

Heat-bath algorithmic cooling with correlated qubit-environment interactions

Abstract: Cooling techniques are essential to understand fundamental thermodynamic questions of the lowenergy states of physical systems, furthermore they are at the core of practical applications of quantum information science. In quantum computing, this controlled preparation of highly pure quantum states is required from the state initialization of most quantum algorithms to a reliable supply of ancilla qubits that satisfy the fault-tolerance threshold for quantum error correction. Heat-bath algorithmic cooling has b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…Specially prepared common bath can also be used for the creation of non-decaying entangled states in multi-qubit systems [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Specially prepared common bath can also be used for the creation of non-decaying entangled states in multi-qubit systems [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In practice, however, the qubits generally possess correlations of both classical and quantum origin, generated thermally and through interactioninduced entanglement respectively. Here, we generalize HBAC to allow the presence of correlations -and we show that these correlations provide a resource that can be used to improve the efficiency of HBAC methods beyond previously established limits.Indeed, recent work has suggested that quantum correlations are important in work extraction and entropy flows in cooling protocols [15][16][17][18][19][20]. However, current algorithms such as PPA (Partner Pairing Algorithm [4, 9]) do not make use of correlations in the system.…”
mentioning
confidence: 99%
“…Indeed, recent work has suggested that quantum correlations are important in work extraction and entropy flows in cooling protocols [15][16][17][18][19][20]. However, current algorithms such as PPA (Partner Pairing Algorithm [4,9]) do not make use of correlations in the system.…”
mentioning
confidence: 99%
See 2 more Smart Citations